Differential Neuroprotection of Selective Estrogen Receptor Agonists against Autonomic Dysfunction and Ischemic Cell Death in Permanent versus Reperfusion Injury - Barry J. Connell; Tarek M. Saleh (Hindawi Limited, 2011)
In the present study, we tested the hypothesis that selective activation of estrogen receptor subtypes (ERα and ERβ) would be neuroprotective following ischemia and/or ischemia-reperfusion, as well as prevent the associated autonomic dysfunction. The selective ERα agonist, PPT, when administered 30 min prior to occlusion of the middle cerebral artery (pMCAO), resulted in a dose-dependent neuroprotection as measured 6 hours postpermanent MCAO, but not following 30 mins of MCAO followed by 5.5 hrs of reperfusion (I/R). In contrast, 30 min pretreatment with the selective ERβ agonist, DPN, resulted in a dose-dependent neuroprotection following I/R, but was not protective following pMCAO. Both drugs prevented the ischemia-induced autonomic dysfunction as measured by a decrease in the baroreceptor reflex sensitivity (BRS). The data presented here suggest a differential role of each ER subtype in targeting the mechanisms of cell death that occur in ischemia versus reperfusion injury.